Japan's answer to the economic demands of an ageing population. (16th October 2012) - Takasaki, Yohsuke; Kawachi, Ichiro; Brunner, Eric J
Abstract : Japan's ageing population and prolonged recession are putting enormous strain on the national budget. Yohsuke Takasaki, Ichiro Kawachi, and Eric Brunner explain the problems and what the government is doing to tackle them